Application of Cost Reduction Tools in Manufacturing Organizations at Pokhara - Sharma, Devilal (Janapriya Journal of Interdisciplinary Studies, 2018)
Today’s business organization’s success highly depends upon the satisfaction of customer needs and wants since it become the age of globalization. All the manufacturing organizations of Pokhara valley are needed to mass customize their product as the requirement of the customer and satisfy to their needs and wants. For this purpose, organizations have to use the modern technology. This study aims to evaluate the application of cost reduction tools in Nepalese manufacturing organizations with reference to Pokhara valley. Out of total manufacturing firm, only 10 organizations have been selected at least two samples from each stratum out of the target population. Primary data have been collected through the structured questionnaires by distributing it to the production manager or finance manager of the concerned organization. The information has been collected through unit visits. An empirical investigation has been conducted in order to find out various aspects of cost reduction tools. The major tool used for this purpose is the questionnaire. Nepalese manufacturing organizations are selecting the purchase of raw material, production planning and control as the area of reducing their cost. All of the organizations are conscious about TQM as the technique of cost reduction. Most of the organizations are applying product line rationalization, supply chain management, KAIZEN system, reengineering as the technique of cost reduction. Most of the organizations are not applying the Design for manufacturability and concurrent engineering, on demand lean production, build to order, part standardization, Just in Time production system as the tools of cost reduction. Janapriya Journal of Interdisciplinary Studies, Vol. 6 (December 2017), page: 45-59